2021
DOI: 10.1158/0008-5472.can-20-2701
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin-Specific CAR T Cells Target Ovarian Cancer

Abstract: New therapeutic options for patients with ovarian cancer are urgently needed. Therefore, we evaluated the efficacy of two second-generation mesothelin (MSLN)-directed CAR T cells in orthotopic mouse models of ovarian cancer. Treatment with CAR T cells expressing an MSLN CAR construct including the CD28 domain (M28z) significantly prolonged survival, but no persistent tumor control was observed. Despite lower response rates, MSLN-4-1BB (MBBz) CAR T cells induced long-term remission in some SKOV3-bearing mice. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 38 publications
2
68
0
Order By: Relevance
“…When MSLN-overexpressing tumor-bearing mice were treated with a high dose of CAR T cells, complete remission of pancreatic cancer was observed in all groups treated with MSLN-CAR T MS501 BBz, 28z, and 28BBz. These results demonstrated that the MSLN-CAR T cells had higher anti-tumor efficacy than that of previously reported MSLN-targeting CAR T cells, which showed anti-tumor effects on a variety of solid tumors, including ovarian, gastric, and pancreatic cancer [( [36] , [37] , [38] , [39] ]. While the 3rd generation CAR T MS501 28BBz showed off-target toxicity, as well as high tumor-killing efficacy, the 2nd generation CAR T MS501 BBz and 28z had comparable or slightly higher tumor-killing efficacy and very low off-target toxicity.…”
Section: Discussionmentioning
confidence: 62%
“…When MSLN-overexpressing tumor-bearing mice were treated with a high dose of CAR T cells, complete remission of pancreatic cancer was observed in all groups treated with MSLN-CAR T MS501 BBz, 28z, and 28BBz. These results demonstrated that the MSLN-CAR T cells had higher anti-tumor efficacy than that of previously reported MSLN-targeting CAR T cells, which showed anti-tumor effects on a variety of solid tumors, including ovarian, gastric, and pancreatic cancer [( [36] , [37] , [38] , [39] ]. While the 3rd generation CAR T MS501 28BBz showed off-target toxicity, as well as high tumor-killing efficacy, the 2nd generation CAR T MS501 BBz and 28z had comparable or slightly higher tumor-killing efficacy and very low off-target toxicity.…”
Section: Discussionmentioning
confidence: 62%
“…Clinical trials using MSLN-directed CAR T cells using a single-chain variable fragment (ScFv) format have demonstrated potential but with limited effect [10, 11, 21, 31]. No MSLN-directed CAR T cells based on the VH domain has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, 4–1BB-containing PSCA-directed CAR T cells show more durable antitumor responses compared with CD28-containing CAR T cells [11, 33]. In ovarian cancer, both CD28- and 4–1BB-containing CAR T cells were able to control SKOV3 cells and prolong the mice survival [21]. In our study, 4–1BB-containing VH 3C9 CAR T cells were effective in inducing tumor toxicity in vitro with 40%-80% killing of both AsPC-1 cells (pancreatic cancer) and NCI-H2452 (mesothelioma) without off target toxicity, demonstrating the possibility of using a VH domain in a CAR construct.…”
Section: Discussionmentioning
confidence: 99%
“…For ovarian carcinoma, recent preclinical studies in vivo showed that it is possible to restore the functions of tumour-specific checkpoint blockade in MSLN-directed CAR T cells using different substances [70][71][72].…”
Section: Chimeric Antigen Receptor T Cell (Car T) Therapymentioning
confidence: 99%